Participation of civilians in Catalonian clinical research and health care institutional ethical review committees - Moharra, Montse; Pons, Joan M. V.; Almazán, Cari; Quintana, Salvador (Acta Bioethica, 2018)
To know the level of participation of patients, users and civilians in scientific ethical review committees (SERC) and health care ethical review committees (HCERC) accredited in Catalonian. Materials and methods: Descriptive transversal study using an opportunistic sample of 30 SERC and HCERC. A questionnaire was filled out addressed to presidents and consumer or civilian (lay member) representatives. For the interpretation of results means and standard deviations were analyzed. Answers to open texts questions were analyzed using qualitative content analysis. Results: 12 committees (40%) accepted to participate; 15 interviews were carried out (9 SERC members and 6 HCERC members): 8 person to person, 4 by phone and 3 by email. SERC Results: Of 7 SERC interviewed, 2 have a civilian representative in the committee. The profile was a woman of administrative profession and an auditor accountant man, both older than 50 years. HCERC Results: Of 5 HCERC participating, 2 declared having a civilian representative. The profile was a woman of administrative profession and a man teacher, both older than 50 years. Discussion: Currently, there is low civilian/patient representation in institutional ethical review committees. Today, the need to incorporate the point of view of the civilian/patient is a debatable issue, being unknown the suitable profile and their representativeness is under discussion.